Investigating the level of glaucoma awareness and perception of its risk factors in Anambra State, Nigeria. (July 2018) - Okoye, R.S.; Bell, L.; Papadopoulos, I.
Abstract: Objectives: The purpose of this study was to investigate the level of awareness of glaucoma and perception of its risk factors in Anambra State, and to examine and evaluate the health seeking behaviour of this target population and its relationship with the development glaucoma. Study design: This is a qualitative study that utilised face-to-face semi-structured interviews to investigate the level of glaucoma awareness in the state. Methods: Purposive, non-random sampling technique was used to recruit the participants, and data were collected from 28 participants [aged 21–73 years] using semi-structured interview. The resulting data were analysed using Nvivo 10 software and Interpretative phenomenological analysis framework. Results: Of the 28 interviewees, 15 (53.6%) live in urban areas, and 13 (46.4%) live in the rural areas; 11 (39.3%) of the participants were male and 17 (60.7%) were females. In this study, people with more education, and people that live in the urban areas tend to have heard about glaucoma compared with people with less education, and who live in the rural areas; although this sample was too small to make substantive claims. Glaucoma was perceived as 'a dangerous eye disease that can cause blindness if not treated early; serious eye problem; an incurable eye problem that can eventually result to blindness, and a dangerous eye problem that can easily render a person blind'. Four a priori themes and ten emergent themes were identified. Conclusions: There is low awareness of glaucoma in this population, and this encourages people to indulge in certain risk behaviours that could predispose them to glaucoma. Therefore, providing sustained health promotion programmes and improved eye care services could help this population immensely in the current struggle against glaucoma blindness. Highlights: My mother taught me how to make use of aloe vera, ginger and garlic. They have not even for one day organised a seminar about eye and causes of eye problems. My sight is normal, why will I go and be looking for problem while there is none? For some participants, it was sheer mistrust and fear of exploitation. Poverty has been a major determinant of health in this population.